2017
DOI: 10.19082/3720
|View full text |Cite
|
Sign up to set email alerts
|

The examination of quality of pregnancy care based on the World Health Organization’s “Responsiveness” model of selected pregnant women in Tehran

Abstract: IntroductionThe World Health Organization (WHO) Responsiveness model showing the ability of health systems in fulfilling people’s expectations in connection with nonclinical aspects is an appropriate pattern to assess healthcare. The purpose of this study was to determine the status of pregnancy care provisions based on the responsiveness model.MethodsThis was a cross-sectional study conducted by randomly sampling 130 women visiting selected hospitals in Tehran in 2015. A researcher-made questionnaire based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…This result is concurrent with other studies in Iran,51 Tanzania21 and a four-country survey in four low-income and middle-income courtiers 52. On contrarily, this finding was lower than the study in Tehran, Iran 53. The possible explanation for the low achievement of basic amenity could be because this study was conducted after a conflict in the study area that resulted in damage to basic amenities in health facilities.…”
Section: Discussionsupporting
confidence: 83%
“…This result is concurrent with other studies in Iran,51 Tanzania21 and a four-country survey in four low-income and middle-income courtiers 52. On contrarily, this finding was lower than the study in Tehran, Iran 53. The possible explanation for the low achievement of basic amenity could be because this study was conducted after a conflict in the study area that resulted in damage to basic amenities in health facilities.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the experience of pregnant women, the 'quality of basic amenities' was highest-rated, meanwhile the 'prompt attention' was the worst. 16 'Confidentiality' was the best in both studies Sajjadi et al and Ughasoro et al, 85% and 68.9%, respectively. At the meantime, the 'autonomy' and 'choice of provider' were the worst, 52% and 41.9%, respectively.…”
Section: Domains Of Responsivenessmentioning
confidence: 80%
“…9 A study conducted in Nigeria revealed that 59% of clients who sought specialist care in tertiary referral hospitals reported good or very good responsiveness 33 and this resembled the level of responsiveness (67%) rated by the diabetic patients in one of the studies in Iran. 27 In two studies, the women while pregnant 16 and post-delivery 13 have shown their satisfaction as a result of the high level of responsiveness at their hospitals.…”
Section: Level Of Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…In CON domain, the privacy of information and medical records was the most paramount for patients in both departments, and this was consistent with some former studies 18,27,28 . It should be noted that the siege and related nancial hardship and economic decline, staff burnout, shortages of in healthcare workforce, and the problem in remuneration system may adversely affect the staff commitment, and ultimately reduced responsiveness performance, particularly PA domain 27,29 .…”
Section: Factors Affecting Responsivenessmentioning
confidence: 99%